Case Report: A case of progressive encephalopathy with or without lipodystrophy caused by BSCL2 variant and literature review - Wang, Yao; Guo, Jing; Zhang, Peiqi; Liu, Fang; Li, Hua (Frontiers in Genetics, 2025)
ObjectivesTo describe a case of Progressive Encephalopathy with or without Lipodystrophy (PELD), characterized by a late onset of neurological regression at 9 years old, due to a homozygous c.974dupG variant in the BSCL2 gene.MethodsAn 11-year, 9-month-old girl with repeated seizures over 2 years underwent clinical assessment and genetic investigation. We also reviewed the published literature.ResultsThe patient exhibited mild intellectual disability, a lipodystrophic appearance, precocious puberty, voracious appetite, elevated transaminase levels, hyperlipidemia, hypercortisolism, hepatomegaly, fatty liver, and splenomegaly. Motor and cognitive regression occurred at 9 years. A homozygous pathogenic variant c.974dup (p.Ile326HisfsTer12) in exon 7 of BSCL2 (NM_001122955.4) was identified. Despite multiple antiseizure medications, seizures were refractory, leading to status epilepticus and rapid death after genetic diagnosis.ConclusionWe confirm that the BSCL2 c.974dupG variant is a cause of PELD. Regression may occur later than previously reported. Literature review suggests that the c.974dupG variant may present a milder phenotype compared to the classic c.985C>T variant. Early genetic testing and diagnosis are crucial for improving outcomes in rare neurodegenerative disorders like PELD.